2009
DOI: 10.1245/s10434-009-0761-5
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Gastrointestinal Stromal Tumors of the Duodenum

Abstract: Based on the fact that type of operation was not correlated to operative risk and disease recurrence, limited operation rather than PD should be attempted for duodenal GIST without involvement of papilla of Vater to preserve more pancreas parenchyma, duodenum, and common bile duct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
50
0
20

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 21 publications
3
50
0
20
Order By: Relevance
“…Similar survival rates have been reported for patients treated with pancreatico-duodenectomy and simple resection [13]. Therefore, simple resection with negative margins should be the preferred treatment, when possible [15].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Similar survival rates have been reported for patients treated with pancreatico-duodenectomy and simple resection [13]. Therefore, simple resection with negative margins should be the preferred treatment, when possible [15].…”
Section: Discussionsupporting
confidence: 67%
“…However, there is no certain consensus on treatment of tumors located in the duodenum. There are different opinions about the respective benefits of pancreatico-duodenectomy and wedge resection [13].…”
Section: Discussionmentioning
confidence: 99%
“…Studies illustrated that compared to the LR group, no statistical significance in disease recurrence was found in the PD group [7, 19, 27, 28]. Also, a meta-analysis confirmed that the oncologic outcome of patients with DGIST was more likely to be dependent on tumor biology rather than the type of surgical procedure [6].…”
Section: Discussionmentioning
confidence: 99%
“…Uehara reports an even higher proportion of 40 % of patients treated by duodenopancreatectomy for duodenal GIST [21]. There have been some large case series reported more recently reiterating the continued dilemma over the surgical treatment of duodenal GISTs [20,22,23]. The literature search that we performed revealed that these lesions can be easily mistaken for an adenocarcinoma and this subsequently leads to treatment with a pancreaticoduodenectomy rather than an organ-sparing procedure.…”
Section: Discussionmentioning
confidence: 99%